TINGKAT KEPUASAN PESERTA GADJAH MADA MEDICAL CENTER (GMC) TERHADAP MUTU PELAYANAN KESEHATAN (SATISFACTION LEVEL OF GADJAH MADA MEDICAL CENTER (GMC) MEMBERS TOWARD HEALTH SERVICE QUALITY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Background: Gadjah Mada Medical Center (GMC) is a clinic which most of its pa¬tients are health insurance member and implementing managed care concepts. It was established to overcome students' health problems and rising health service cost. The developing science and technology leads to demand to improve health service and professionalism. Therefore, in accordance to the GMC vision, service quality must be the first priority. Measuring member satisfaction level is one way to improve quality service. This study was aimed at finding out the satisfaction level of members to GMC services and correlation factors with satisfaction level, and the related factors, also to obtain representation about members' expectation of GMC service. Methods: This was a quantitative and qualitative cross sectional study. The system¬atic random sampling technique with 250 respondents was used to obtain the pri¬mary care (RJTP) sample. The measurement was taken from disconfirmation-scale, closed questionnaires and opened questions. While research for the referral out pa¬tient care (RJTL) and the in-patient (Ranap) services were performed through fo¬cused group discussion (FGD). Results: The result of primary care (RJTP) showed that 4,4% respondents are not satisfied, 82.0% are satisfied enough, and 13.2% are satisfied, and 0,4% are very satisfied. Experience become member of the other health insurance is significantly correlated with satisfaction level (p < 0.05). Responsiveness dimension was most dominant to satisfaction level. Respondents expectation are mostly about waiting room comfort, waiting time, quality and supply of drug, accurate, information and empathy of doctor. Expectation for RJTL and in patient are about the improvement in financial administration, medical services, and paramedics. Conclusion: The members are satisfied with the service but still have a high expec¬tation for improvement. The satisfaction level is significantly correlated with experience become member of the other health insurance. Keywords: health insurance, managed care, quality, member satisfaction, member expectation.